Diet Compliance Against Blood Pressure Control in Hypertensive Patients in Tegalgundil public Health Center, North Bogor District: A Longitudinal Study (Indian Journal of Public Health Research & Development, 2020)
Background: One contributing factor of deaths due to uncontrolled hypertension is dietary disobediencebecause food affects blood pressure. Thus, Dietary Approach to Stop Hypertension for Indonesian (DASHI)is recommended, because it can control blood pressure in hypertensive patients.Objectives; This study aims to investigate the impact of DASHI diet adherence on systolic blood pressure(SBP) and diastolic blood pressure (DBP) changes in hypertensive patients.Material and Method: We performed a longitudinal study from May to September 2017 using primarydata and non-random sampling method with purposive sampling. The data on blood pressure, food intake,physical activity, medication adherence, stress levels, smoking habits, routine blood pressure checks androutine weighting habits was collected via interviews, questionnaires and measurements.Result: For SBP, the first- and second-month average measurement in non-adherent respondents of theDASHI diet was 145.68 and 148.82 mmHg, respectively. Conversely, the third-month average measurementin obedient respondents was 137.88 mmHg. For DBP, the first-, second- and third-month average measurementin non-adherent respondents was 88.61, 87.84 and 84.48 mmHg, respectively.Conclusion: This study establishes a difference in SBP and DBP changes depending on the DASHIdiet compliance based on the comparison of measurement results, including the first- and second-monthmeasurement compared to third after controlling smoking and medication compliance covariates.
Keywords: compliance, hypertension, blood pressure